Effect of Protein Additives on Acetylene Reduction (Nitrogen Fixation) by Rhizobium in the Presence and Absence of Soybean Cells - Anderson, Stephen J. (1976)
The effect of protein additives on acetylene reduction (N(2) fixation) by Rhizobium associated with soybean cells (Glycine max [L.] Merr.) in vitro was studied. Acetylene reduction was promoted on the basal medium supplemented with 1.4 mg of N/ml supplied as aqueous extracts of hexane-extracted soybean, red kidney beans (Phaseolus vulgaris L.), or peas (Pisum sativum L.). Commercial samples of α-casein, or bovine serum albumin also promoted acetylene reduction at a concentration of 1.4 mg of N/ml of basal medium, but egg albumin supplying an equal amount of nitrogen to the basal medium completely suppressed acetylene reduction. Autoclaving the aqueous extract of hexane-extracted soybean meal had no effect on its ability to promote acetylene reduction. The presence of 40 mm succinate decreased acetylene reduction with leguminous proteins supplying 1.4 mg of N/ml but promoted acetylene reduction by Rhizobium 32H1-soybean cell associations on media containing α-casein, bovine serum albumin, or egg albumin suppling 1.4 mg of N/ml. Similar results were obtained with both cowpea Rhizobium 32H1 and Rhizobium japonicum 61A96. Pure cultures of Rhizobium 32H1 developed acetylene-reducing activity in the presence of soybean extract on basal agar medium and in vermiculite supplied with N-free mineral salts plus crude soybean meal. The results suggest that in certain situations, free living Rhizobium may reduce N(2) under field conditions.